Isotropy subgroups of the 230 crystallographic space groups - Stokes, Harold T. (World Scientific, 1988)
This book gives a rather exhaustive list of isotropy subgroups of the 230 crystallographic space groups. The symmetry changes for the vast majority of observed phase transitions in crystalline solids can be found in the list. With each entry, information is given concerning both physical and abstract characteristics of the phase transitions.